2021
DOI: 10.3390/ijerph18094611
|View full text |Cite
|
Sign up to set email alerts
|

Association between Compliance with Movement Behavior Guidelines and Obesity among Malaysian Preschoolers

Abstract: A daily balance of physical activities, sedentary behaviors and sleep are important for maintaining the health of young children. The aim of this study is to explore the association between 24-h movement behavior of Malaysian children aged 4 to 6 years with weight status. A total of 230 preschoolers were recruited from 22 kindergartens in Kuala Lumpur. Physical activity was assessed by Actical accelerometer while screen time and sleep duration were proxy-reported by parents. Children spent on average 5.5 ± 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…On the other hand, other studies [ 53 , 54 ] have shown that for decreasing obesity levels in adolescents, ACS could only be part of a multicomponent approach, being as important as PA and diet. Therefore, it seems difficult to analyze the relationship between ACS and obesity levels alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, other studies [ 53 , 54 ] have shown that for decreasing obesity levels in adolescents, ACS could only be part of a multicomponent approach, being as important as PA and diet. Therefore, it seems difficult to analyze the relationship between ACS and obesity levels alone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems difficult to analyze the relationship between ACS and obesity levels alone. As we know, childhood obesity could be reduced by multi-component modifiable behavioral changes, including physical activity, but also sedentary behavior and dietary patterns [ 53 ]. Recently, the focus has shifted to following a more integrated approach in which it is recognized that 24-h movement behaviors are co-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a computed average from 11 different countries, 13 percent of under 5-year-old children meet all the guidelines [ 20 ], when, for example, in some urban areas outside of Europe rates are reported to be as low as three percent [ 21 , 22 ]. Compared with PA and sleep, the ST guideline is met more rarely [ 12 , 20 , 22 , 23 ]. In Finland, the prevalence of meeting all the guidelines is reduced from 52 percent at the age of 6 years to 25 percent at the age of 8 years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need to include creative and appealing play elements in implementing children's activities to complement the learning and teaching processes. Unfortunately, most teachers in preschools are prone to applying direct teaching pedagogy without prioritizing play (Lee et al, 2021) due to their lack of knowledge and skills in the play approach, which inadvertently affects their familiarity with materials and play elements generally used for teaching (Blackwell et al, 2016;Padmavathi, 2017). Such inadequacies of teachers, which result in their less appealing and meaningful delivery methods (Mishra & Koehler, 2006), threaten children's interests in what is being taught and make the learning process formidable (Baranovich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%